1996
DOI: 10.1177/011542659601100389
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: The Nutrition Screening Initiative: A 5‐Year Perspective

Abstract: A history of the goals, activities, and accomplishments of the Nutrition Screening Initiative (NSI) is provided. A commentary on the development and intended use of the NSI's self-assessment and screening tools is given to facilitate selection of feeding devices for older Americans who need nutrition care. Additional questionnaires and interventions designed to address the needs identified through the NSI's standardized, interdisciplinary approach to the assessment of nutritional risk are described and their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Those older Americans most vulnerable to malnutrition are the oldest old (aged 85 and older), minority group members, women, those with limited income or resources, those isolated from family or friends, those who lack access to adequate diet, and those whose selfcare abilities are limited [12]. With the population of older people steeply on the rise, the number of those in nursing homes decreasing and the known higher risk for malnutrition in the oldest of the older population, home-based nursing and community-based efforts to identify, prevent, and treat malnutrition and its antecedents are a vital part of preventive healthcare and thus are important for the long-term health of the population.…”
Section: Focus On the Oldest Old (Elderly)mentioning
confidence: 99%
See 3 more Smart Citations
“…Those older Americans most vulnerable to malnutrition are the oldest old (aged 85 and older), minority group members, women, those with limited income or resources, those isolated from family or friends, those who lack access to adequate diet, and those whose selfcare abilities are limited [12]. With the population of older people steeply on the rise, the number of those in nursing homes decreasing and the known higher risk for malnutrition in the oldest of the older population, home-based nursing and community-based efforts to identify, prevent, and treat malnutrition and its antecedents are a vital part of preventive healthcare and thus are important for the long-term health of the population.…”
Section: Focus On the Oldest Old (Elderly)mentioning
confidence: 99%
“…Two other instruments (the Level I and Level II screens- Table 4) focused more on assessment by healthcare professionals, were less widely used, and (to our knowledge) have not been validated. The NSI produced a variety of other checklists including the Oral Health Checklist, Medications Use Checklist, Feeding Difficulties Checklist, and Nutrition Counseling Checklist [12]. …”
Section: Screening and Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It was validated using both retrospective simulation and prospective validation methods. Both methodologies showed that older persons with higher Checklist scores were likely to have the lowest levels of nutrient intakes compared to recommended allowances and be at increased risk for adverse health events (Barrocas et al, 1996;White, 1996). The intended uses of the Checklist were to increase public awareness of the importance of nutrition and health, and to initiate dialogue between health professionals and older adults concerning adequate nutrition.…”
Section: Introductionmentioning
confidence: 99%